Incorporating shared tutorial videos in learning photo-editing skills among language students / Fairuz Husna binti Mohd Yusof ...[et al.] - Mohd Yusof, Fairuz Husna; Ismail, Othman; Isa@Darami, Aflah (Universiti Teknologi MARA, Kedah, 2020)
In the midst of face-to-face class lessons in which plethora of knowledge could be exchanged and shared, some students may not be able to understand the content instantaneously as their classmates may do as there is 'too much information' that needs to be comprehended especially in learning hands-on skills like photo-editing programme. According to Sweller (1999), learning activity as such is considered as high-element interactivity, in which its material is difficult to understand. For this study, students were expected to grasp the skills of photo editing in Adobe Photoshop programme. This study intended to investigate the learning experiences of 23 students of Diploma in English for Professional Communication in acquiring photo-editing skills through the sharing of tutorial videos as an additional source of learning to reinforce their understanding. For this study, the tutorial videos provided steps on how to use a specific tool in Adobe Photoshop prepared by each student that was later shared on Google Classroom. A set of questionnaires was used to get the information on their perceptions' of using tutorial videos to enhance their understanding. This study would contribute to the teacher's understanding on how the usage of shared tutorial videos could minimise the effect of cognitive overload towards students' learning and how it facilitates their understanding towards their lessons